The effect of e-WOM, halal awareness, influencer marketing and lifestyle to the purchase decision of imported packaged food products - Shanaya Rifiana Dewi; Edy Yusuf Agung Gunanto (Fakultas Ekonomi dan Bisnis Islam UIN Salatiga, 2023)
Purchasing decisions are part of the consumer's behavior to determine which products to consume. Many factors can affect purchasing decisions. This study aims to analyze the factors affecting consumer purchasing decisions on imported packaged food products. The data was obtained through a questionnaire distributed online through Google form with a sample of 200 respondents who had bought or consumed imported packaged food products in Jakarta. Structural Equation Modeling (SEM) with Partial Least Square (PLS) techniques using SmartPLS 3.0 analysis tools was used in this study. Results show that the e-WOM, halal awareness, influencer marketing and lifestyle variables have a positive significant effect on the purchase decision of imported packaged food products.